Metal Flux from Dissolution of Iron Oxide Grain Coatings in Sandstones. (18th May 2021) - Parnell, J.; Wang, X.; Raab, A.; Feldmann, J.; Brolly, C.; Michie, R.; Armstrong, J.
Abstract : Iron oxide grain coatings in red sandstones contain trace metals that are released upon dissolution of the coatings. Analyses by ICP-MS following acid leaching of the grain coatings show that the dissolved metals can constitute an ore-forming fluid, as hypothesized in models for sandstone-hosted ore deposits. Median compositions of 37 samples, mostly of Triassic to Devonian age, from across Britain and Ireland are 6.3 ppm copper, 2.4 ppm cobalt, 10.1 ppm vanadium, and 0.3 ppm uranium. These contents at the basin scale are adequate to form the observed range of ore deposits in red beds. The migration of hydrocarbons or brines can cause the dissolution of grain coatings and contributes to controlling the distribution of ore deposits. Future measurements should test red beds derived from uplifted, mineralized plate margins, in which sandstones may be preloaded with ore metals.